An ace up their sleeve: a transcriptomic approach exposes the AceI efflux protein of Acinetobacter baumannii and reveals the drug efflux potential hidden in many microbial pathogens - Hassan, Karl A.; Elbourne, Liam D.; Li, Liping; Hewawasam Gamage, Hasinika K.; Liu, Qi; Jackson, Scott M.; Sharples, David; Kolstø, Anne-Brit; Henderson, Peter J.; Paulsen, Ian T. (Frontiers in Microbiology, 2015)
The era of antibiotics as a cure-all for bacterial infections appears to be coming to an end. The emergence of multidrug resistance in many hospital-associated pathogens has resulted in “superbugs” that are effectively untreatable. Multidrug eﬄux pumps are well known mediators of bacterial drug resistance. Genome sequencing efforts have highlighted an abundance of putative eﬄux pump genes in bacteria. However, it is not clear how many of these pumps play a role in antimicrobial resistance. Eﬄux pump genes that participate in drug resistance can be under tight regulatory control and expressed only in response to substrates. Consequently, changes in gene expression following antimicrobial shock may be used to identify eﬄux pumps that mediate antimicrobial resistance. Using this approach we have characterized several novel eﬄux pumps in bacteria. In one example we recently identified the Acinetobacterchlorhexidine eﬄux protein (AceI) eﬄux pump in Acinetobacter. AceI is a prototype for a novel family of multidrug eﬄux pumps conserved in many proteobacterial lineages. The discovery of this family raises the possibility that additional undiscovered intrinsic resistance proteins may be encoded in the core genomes of pathogenic bacteria.